Aging, Social Security Design, and Capital Accumulation - Antoine Dedry; Harun Onder; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper analyzes the impact of aging on capital accumulation and welfare in a country with a sizable unfunded social security system. Using a two-period overlapping generation model with potentially endogenous retirement decisions, the paper shows that the type of aging, i.e. declining fertility or increasing longevity, and the type of unfunded social security system, i.e. defined contributions or defined benefits, are important in understanding this impact. Moreover, the analysis provides a refinement to common policy recommendations that favor eliminating mandatory early retirement regulations in aging societies: aging leads to a greater increase in welfare when it is driven by an increasing longevity and the retirement age is unregulated. In comparison, when aging is driven by a decreasing fertility rate, a mandatory retirement system fosters more savings and, thus, income and welfare, in a closed economy with unfunded pension system based on defined contributions.
Keywords: H20; F42; H80; 330; aging; public finance sustainability; social security